2005
DOI: 10.1002/esp.1176
|View full text |Cite
|
Sign up to set email alerts
|

The influence of both process descriptions and runoff patterns on predictions from a spatially distributed soil erosion model

Abstract: Spatially distributed, process-based erosion models have been built to predict both erosion and deposition rates and patterns. However, predictions by these models often do not meet our expectations. There are several possible reasons for this, which can be subdivided into three groups: (i) process descriptions within the models may be incomplete or incorrect, leading to structural errors (model error); (ii) parameterization is difficult leading to a high degree of uncertainty regarding model inputs (input err… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 20 publications
0
20
0
1
Order By: Relevance
“…It seems clear that, for getting reliable estimation of spatial erosion and sediment transport patterns a spatially distributed validation is required, as it has been suggested by some authors (Takken et al 1999(Takken et al , 2005Vigiak 2006). …”
Section: Model Calibrationmentioning
confidence: 99%
See 1 more Smart Citation
“…It seems clear that, for getting reliable estimation of spatial erosion and sediment transport patterns a spatially distributed validation is required, as it has been suggested by some authors (Takken et al 1999(Takken et al , 2005Vigiak 2006). …”
Section: Model Calibrationmentioning
confidence: 99%
“…These and other applications suggest that WATEM/SEDEM is a valid tool for assessing spatial patterns of erosion and sediment flux on the landscape. However, some questions of the model's appliction still arise, such as the need for a spatially distributed calibration (Takken et al, 1999(Takken et al, , 2005Vigiak, 2006) or the importance of processes not included in the model (de Vente et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…La calibración de los parámetros de capacidad de transporte es un aspecto fundamental de WATEM/SEDEM que todavía no ha sido resuelto. Los resultados aquí obtenidos confirman que para obtener una estimación más fiable de la distribución espacial de los procesos de erosión y sedimentación se requiere una calibración y una validación con datos espacialmente distribuidos, tal y como ya ha sido sugerido por otros autores (Takken et al 1999(Takken et al , 2005Vigiak et al, 2006). En el caso de la cuenca experimental de Arnás, el proceso de calibración consistió en realizar un gran número de simulaciones (n=100) para el periodo 1963-2003, modificando discretamente los valores de ktc min y ktc max .…”
Section: Calibración De Watem/sedemunclassified
“…Moreover, the measurement scale is often very different from the model scale. Some relevant examples are WEPP [Laflen et al, 1991a], EUROSEM [Morgan et al, 1998] and LISEM The conceptual or parametric approach is probably the methodology with the best perspective, although its calibrated parameters lack of physical meaning [Dickinson et al, 1986;Ferro and Minacapilli, 1995;Takken et al, 2005]. In the last 15 years, many conceptual models were developed, such as LASCAM [Viney and Sivapalan, 1999] and CASC2D-SED [Johnson et al, 2000].…”
Section: According To the Conceptualizationmentioning
confidence: 99%
“…The authors demonstrated that the uncertainty was higher in the UK catchments rather than the USA catchments, where the model was developed, in spite of the physical bases of WEPP, which should be valid all over the world. In literature, many other papers show the sensibility of sediment models to their parameters [Folly et al, 1999;Brazier et al, 2000;Takken et al, 2005].…”
Section: Main Limitations Of Sediment Modelsmentioning
confidence: 99%